Explaining the burden of cultural factors on MS disease: a qualitative study of the experiences of women with multiple sclerosis - Fahimeh Pourhaji; Mousa Mahdizadeh Taraghdar; Nooshin Peyman; Jamshid Jamali; Hadi Tehrani (BMC, 2024)
Abstract Background Multiple sclerosis (MS) is a debilitating, non-traumatic disease that is common among young adults. Cultural factors, as background factors, can affect how patients adapt and their quality of life. This study aimed to explain the burden of cultural factors on Multiple sclerosis. Methods This study was conducted with a qualitative approach and conventional content analysis among women with Multiple sclerosis in Mashhad. The data were collected through semi-structured interviews with women with MS. Fifteen patients with Multiple sclerosis were selected using purposeful sampling. The Graneheim and Lundman method was used to analyze the collected data. The transferability of the study was evaluated using the Guba and Lincoln criteria. MAXQADA 10 software was used to manage and analyze the data. Results In explanation of the cultural factors of patients with Multiple sclerosis, one category (cultural tensions) and five subcategories (forced communication with spouse's family, definition of women's role in society, people's behavior, social beliefs and isolation of the patient) were extracted. Conclusion The results obtained in this study show that female MS patients face various concerns. Overcoming these challenges require a change in the attitude of people in the society towards women with MS, which is important in the context of formulating practical policies to create a suitable culture. Adopted policies should aim to internalize the culture of changing society's views of female MS patients. Therefore, the authors argue that there is a need for cultural policies, followed by the systems implementing these policies to consider the challenges mentioned in this study as a priority for MS patients.